Self-Regulated Dynamical Criticality in Human ECoG - Solovey, Guillermo; Miller, Kai J.; Ojemann, Jeffrey; Magnasco, Marcelo O.; Cecchi, Guillermo A. (Frontiers in Integrative Neuroscience, 2012)
Mounting experimental and theoretical results indicate that neural systems are poised near a critical state. In human subjects, however, most evidence comes from functional MRI studies, an indirect measurement of neuronal activity with poor temporal resolution. Electrocorticography (ECoG) provides a unique window into human brain activity: each electrode records, with high temporal resolution, the activity resulting from the sum of the local field potentials of \sim 10^5 neurons. We show that the human brain ECoG recordings display features of self-regulated dynamical criticality: dynamical modes of activation drift around the critical stability threshold, moving in and out of the unstable region and equilibrating the global dynamical state at a very fast time scale. Moreover, the analysis also reveals differences between the resting state and a motor task, associated with increased stability of a fraction of the dynamical modes.